Patterns, patterns, patterns: art and meaning at the crossroads between two opposing forces - Ramírez Calle, Olga (Wiley, 2020)
This article aims to defend the need to recognize the independent role of those cognitive abilities on whose behalf linguistic meaning is introduced from the proper institution of language. I call this capacity “private pattern recognition” (PPR) and argue that it plays an essential part not just in the instauration of linguistic meaning but also in other relevant cognitive phenomena such as artistic creation and understanding. Moreover, it is precisely the failure to separate both aspects that gives rise to important perplexities associated with the underdetermination of meaning. The first part of the article makes a case for this thesis and addresses its compatibility with Wittgenstein's private language argument. It then focuses on the example of art to illustrate the differing roles of private pattern recognition and shared linguistic meaning. The second part of the article focuses on the paradox of resemblance (RP). It (i) considers the difficulties of Williamson's response, (ii) illustrates how they instead support the current thesis, (iii) attempts to delineate how the role of meaning should be understood, and (iv) briefly revisits the rule-following paradox (RFP).
Keywords: Paradojas; Creación artística; Patterns; Family resemblance; Rule-following; art; Meaning